2004
DOI: 10.1097/00006199-200401000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Health Behaviors as Mediators for the Effect of Partner Abuse on Infant Birth Weight

Abstract: Although prospective studies are warranted, nursing care to reduce smoking and promote adequate weight gain in all women along with support for women's efforts to seek safety from abuse may help to improve birth outcomes and promote maternal well-being.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 26 publications
0
32
0
3
Order By: Relevance
“…Directly, a physical or sexual assault involving abdominal trauma can cause abruptio placenta leading to fetal death, abortion, PROM, preterm labor, and delivery of a preterm infant [4,5], while indirectly, adverse outcomes may arise from associated prenatal stress [5]. For low birth weight and preterm labour, the actual mechanism involved has been linked to maternal prenatal stress [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Directly, a physical or sexual assault involving abdominal trauma can cause abruptio placenta leading to fetal death, abortion, PROM, preterm labor, and delivery of a preterm infant [4,5], while indirectly, adverse outcomes may arise from associated prenatal stress [5]. For low birth weight and preterm labour, the actual mechanism involved has been linked to maternal prenatal stress [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Unlike other research (Bacchus et al, 2003;Bohn & Parker, 1993;Curry & Harvey, 1998;Grimstad et al, 1997;Huth-Bocks et al, 2002;Kearney et al, 2004;Neggers et al, 2004;Parker et al, 1994;Wang & Chou, 2003) that outlines an array of negative consequences for childbirth and the health of mother and newborn, the participants surveyed indicated that they used good health practices and their children were born without major complications and remain healthy. Without a comparison group, it is impossible to determine if this is significant.…”
Section: Discussionmentioning
confidence: 74%
“…Violence during pregnancy is also associated with depression (Amaro, Fried, Cabral, & Zuckerman, 1990;Bacchus, Mezey, & Bewley, 2003;Horrigan, Schroeder, & Schaffer, 2000), substance abuse (Amaro et al, 1990;Grimstad, Schei, Backe, & Jacobsen, 1997;Huth-Bocks et al, 2002;Kodituwakku, Kalberg, & May, 2001;Martin, Beaumont, & Kupper, 2003;Parker et al, 1994), poor nutrition (Bohn & Holz, 1996), and cigarette smoking (Dye, Tollivert, Lee, & Kenney, 1995;Grimstad et al, 1997;Parker et al, 1994). Moreover, women who experience interpersonal violence during pregnancy are at risk for low birthweight babies (Bohn & Parker, 1993;Curry & Harvey, 1998;Grimstad et al, 1997;Huth-Bocks et al, 2002;Kearney, Munro, Kelly, & Hawkins, 2004;Parker et al, 1994) Neggers, Goldenberg, Cliver, & Hauth, 2004;Wang & Chou, 2003), obstetric complications (Bacchus et al, 2003), low maternal weight gain (Parker et al, 1994), infections (Parker et al, 1994), and homicide (Campbell, Soeken, et al, 2000). Battered pregnant women also report more stress and "overload" (Curry & Harvey, 1998), less support from partners (Curry & Harvey, 1998), less overall social support (Amaro et al, 1990;Huth-Bocks et al, 2002), and less happiness about being pregnant (Amaro et al, 1990) than other pregnant women.…”
Section: Impact Of Violence On Pregnancymentioning
confidence: 99%
“…Entre eles, sete foram publicados nos Estados Unidos (Campbell at al, 1999;Shumway et al, 1999;Jagoe et al, 2000;Kearney et al, 2004;Coker, SAnderson, Dong, 2004;Neggers et al, 2004), dois na Inglaterra (Johnson et al, 2003;Bacchus, 2004), um na Suécia (Stenson et al 2001), dois no Brasil (Moraes e Reichenheim, 2002;Menezes et al, 2003) e um no México (Castro e Ruiz, 2004).…”
Section: Prevalência Entre Usuárias De Serviços De Saúdeunclassified
“…Destes treze estudos, nove foram realizados com desenho do tipo corte transversal (Coker, Sanderson, Dong, 2004;Kearney et al, 2004;Johnson et al, 2003;Bacchus, 2004;Moraes e Reichenheim, 2002;Menezes et al, 2003;Castro e Ruiz, 2004) e apresentam a prevalência do fenômeno na população de usuárias estudada, bem como os fatores a ele associados. Três estudos consistiram em coortes para identificação do impacto da violência na saúde materno-infantil (Neggers et al, 2004;Jagoe et al, 2000;Shumway et al, 1999) e um deles desenvolveu desenho de caso-controle avaliando a violência na gestação e outros fatores de risco para o baixo peso ao nascer (Campbell at al, 1999).…”
Section: Prevalência Entre Usuárias De Serviços De Saúdeunclassified